We Have an Imaginary Friend in Jesus: What Can Imaginary Companions Teach Us About Religion? - MacKendrick, Kenneth G. (Implicit religion, 2012)
This article investigates the plausibility of using studies of imaginative play to illuminate and explain the contemporary prevalence andpopularity of religious imaginal dialogue. Emphasis is given to conceptual considerations arisingfrom the application of recent findings in the neuroscience of social cognition and cognitive theories of childhood development to the study of religion.